Microplastics in fish muscle tissue: A thematic study of microplastic contamination in wild fish caught from tidal rivers in Sabah state, Borneo, Malaysia - Soo, Chen Lin; Kalwant- Singh; Chen, Cheng Ann
Microplastic contamination in fish poses a risk to human health. The scarcity of previous studies on microplastic contamination in fish, especially in muscle tissue, highlights knowledge gaps in this area. Therefore, the aim of this study was to assess the occur rence, abundance, and characteristics of microplastics in the edible parts of fish caught from tidal rivers in Sabah. A total of 146 fish samples were caught, and microplastics were extracted from all muscle tissues. Results indicate that 45.9 % of fish muscle tissue samples were contaminated with microplastics, with an average content of 2.0 ± 4.3 items per individual. Small-sized microplastics (87.6 %), fragments (39.1 %), black color (36.5 %), and viscose (53.4 %) were the predominant characteristics of microplas tics found in fish muscle. Consumption of these microplastic- contaminated fish may pose health risks to local residents of Sabah state.